HUBUNGAN NEUTROPHIL TO LYMPHOCYTE RATIO SEBAGAI FAKTOR PREDIKTIF DEFISIT NEUROLOGIS PADA PASIEN STROKE ISKEMIK AKUT - Adrian Djatikusumo; Poppy Kristina Sasmita; Bryany Titi Santi (NEURONA, 2021)
Introduction: Stroke is defined as a neurological deficit with sudden onset associated with focal and global vascular causes, which leads to morbidity and mortality. In all stages of acute ischemic stroke, an inflammatory process occurs, which is mediated by neutrophils or lymphocytes. Aim: To determine the correlation between neutrophil to lymphocyte ratio (NLR) with neurological deficits or functional outcomes in acute ischemic stroke patients. Methods: This study was conducted using a systematic review method. The studies, filtered through various databases, were assessed for quality and risk of bias using the Newcastle-Ottawa Scale (NOS). Stroke severity and neurological deficits were assessed using the National Institutes of Health Stroke Scale (NIHSS), Scandinavian Stroke Scale (SSS) and modified Rankin Scale (mRS). Results: There were seven studies that met the criteria for the literature search and were assessed as having high quality based on NOS. All included studies stated that there was a significant relationship between NLR and poor stroke functional outcomes in acute ischemic stroke patients (p-value <0.05). The cutoff value of the NLR on the neurological deficits of acute ischemic stroke patients ranged from 2.39 to 4.58 with varying sensitivity and specificity. Discussion: The variations of cutoff, sensitivity and specificity of NLR in predicting neurological deficits could be influenced by the number and characteristics of the sample, race, comorbidity and inclusion and exclusion criteria in the included articles. The significant relationship between NLR and neurological deficits is based on an inflammatory process that occurs at all stages of acute ischemic stroke. Keywords: acute ischemic stroke, functional outcomes, neurological deficits, NLR.